NOVELITY IN GB VIRUS C / HEPATITIS G VIRUS AND ITS CONTROVERSY - Waqar, Ahmed Bilal; Khan, Sanaullah; Idrees, Mohammad (Journal of Ayub Medical College Abbottabad, 2002)
Several novel human RNA viruses were identified in 1995-96 and were partially characterized that apparently can cause acute and chronic hepatitis both in monkeys and humans. These new viruses are related to the flavivirus hepatitis C. It is known to be distinct from other human hepatitis viruses (A, B, C, D, E). Three viruses, identified by investigators at Abbott Labs, have been termed GB-A, GB-B and GB-C. GB-A and GB-B are likely tamarin viruses whereas GB-C infects humans only. All these three viruses are the isolates of the same virus termed HGV, which is positive stranded RNA virus. The genomic sequences of these viruses have been determined by different researchers, which were found to be 1600 nucleotide long. Another group at Genelabs Technologies has identified and determined the complete genomic sequence of a virus they termed hepatitis G virus (HGV). Based on genomic sequence comparisons HGV is probably the same as GB-C. It is a highly controversial virus regarding pathogenecity, mode of transmission and site of replication.